Research on resistance of yeast to organic solvent - ZHENG Xiao-dong; MEI Le-he; FANG Zhe-hong; SUN Ping (浙江大学学报. 农业与生命科学版)
In this article ten strains of yeast were chosen to test their resistance to organic solvents. The results showed that Sccharomyces cerivisiae had stronger resistance than others. The resistance of yeast to organic solvent affected by not only the polarity, toxicity and the dose of the organic solvents, but also the consistence of cell membrane, culture media and others. The resistance of the most of the strains wasn't changed when the concentration of the［Mg］2+ in the media was increased two fold. The growth of the yeasts tested and the resistance of yeasts to organic solvents was obviously affected by temperature.